A Swedish national adoption study of criminality. Issue 9 (July 2014) - Kendler, K. S.; Larsson Lönn, S.; Morris, N. A.; Sundquist, J.; Långström, N.; Sundquist, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background To clarify the role of genetic and environmental factors in criminal behavior (CB), we examined all CB and violent and non-violent subtypes (VCB and NVCB, respectively) in a Swedish national sample of adoptees and their relatives. Method CB was defined by a conviction in the Swedish Crime Register with standard definitions for VCB and NVCB subtypes. We examined adoptees born 1950–1991 (n = 18 070) and their biological (n = 79 206) and adoptive (n = 47 311) relatives. Results The risk for all CB was significantly elevated in the adopted-away offspring of biological parents of which at least one had CB [odds ratio (OR) 1.5, 95% confidence interval (CI) 1.4–1.6] and in the biological full and half-siblings of CB adoptees (OR 1.4, 95% CI 1.2–1.6 and OR 1.3, 95% CI 1.2–1.3, respectively). A genetic risk index (including biological parental/sibling history of CB and alcohol abuse) and an environmental risk index (including adoptive parental and sibling CB and a history of adoptive parental divorce, death, and medical illness) both strongly predicted probability of CB. These genetic and environmental risk indices acted additively on adoptee risk for CB. Moderate specificity was seen in the transmission of genetic risk for VCB and NVCB between biological parents and siblings and adoptees. Conclusions CB is etiologically complex and influenced by a range of genetic risk factors including a specific liability to CB and a vulnerability to broader externalizing behaviors, and by features of the adoptive environment including parental CB, divorce and death. Genetic risk factors for VCB and NVCB may be at least partially distinct.